Pelatihan Keuangan Digital pada UMKM Desa Panda - M. Rimawan; Puji Muniarty; Alwi Alwi; Hanifa Muthiah (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
This community service activity was carried out with the aim of increasing the capacity of Micro, Small, and Medium Enterprises (MSMEs) in Panda Village, Palibelo District, Bima Regency, particularly in the culinary MSME sector in terms of preparing digital-based financial reports. MSMEs often face obstacles in maintaining structured financial records, so intervention in the form of appropriate guidance and training is needed. The solution offered in this activity is the use of the General Accounting (AKU) application which is specifically designed to facilitate digital business financial recording. The community service activity was carried out through three main stages, namely: (1) an initial survey to identify the needs and level of understanding of participants regarding financial reports; (2) direct training and mentoring related to the use of the AKU application, which included an introduction to the application features, practice recording transactions, and simulation of creating financial reports; and (3) evaluation of the results of the activity to assess the effectiveness of the training. The results of this activity showed a significant increase in participants' understanding of preparing MSME financial reports. Before the training, only around 20% of participants had a basic understanding of financial recording. After the training, the level of understanding increased to 80%. Furthermore, 100% of participants were able to operate the AKU application effectively, understand its features, and successfully apply it to record transactions and prepare financial reports for their respective businesses. Thus, this activity has had a positive impact on the digital financial literacy of MSMEs and made a real contribution to supporting more professional and sustainable business management. It is hoped that this training can serve as a model for similar programs in other regions.